The Role of Genes and Genetic Variation in Human Tuberculosis Susceptibility: A Population Perspective - Hasan , Syed Ikramul (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Tuberculosis (TB) is a serious infectious disease caused by Mycobacterium tuberculosis (Mtb) bacteria that affected many people around the world. However, not everyone who was exposed to Mtb got sick, which implied that some genetic factors influenced how people responded to TB infection. The question of whether TB was influenced more by genes or by the environment had been a topic of research for a long time. In this review paper, we examined the findings and difficulties of the studies on the genetic determinants of human TB susceptibility and how much genetic variation contributed to it, from twin and candidate gene studies to genome-wide association studies. This comprehensive review developed into the then-current state of knowledge and the intricate challenges inherent in researching the genetic underpinnings of human susceptibility to TB. The exploration of this genetic aspect spanned a spectrum, from classical twin studies and candidate gene investigations to more contemporary approaches like genome-wide association studies and genetic variation in noncoding RNA analysis. Within this evolving landscape, we highlighted the genes such as TNF, NRAMP, IFN-γ, NOS2, IGR, VDR, TYK2, TLR, MBL, IGRM, ASAP1, AGMO, FOXP1, P2X7, SP110, and UBLCP1 and the mechanisms involved in the development of TB. Furthermore, we explored the role of genetic variation in regulating the immune response to MTB infection collectively with environmental factors. Hence, we also reviewed how environmental factors, such as diet, living conditions, and co-infections, affected the likelihood and severity of TB. Understanding the interplay of genetic and environmental factors allowed us to identify the people who were most vulnerable to TB and design better strategies to prevent and treat it.